FROM FLASH TO ALGORITHM: AESTHETIC AND PRODUCTIVE TRANSFORMATIONS IN ADVERTISING PHOTOGRAPHY - de Lara, Alexandre Torresani (Seven Editora, 2026)
This chapter examines the trajectory of advertising photography over the decades, from the artisanal practices of the twentieth century to the immersive digital productions of 2026. Based on the analysis of award-winning campaigns from major international festivals — Cannes Lions, D&AD, Clio Awards, and Wave Festival —, the study connects formal and aesthetic shifts with technological and cultural change. Using a qualitative bibliographic-analytical approach, supported by Peircean semiotics, Gilbert Durand’s theory of the imaginary, and W.J.T. Mitchell’s visual culture studies, the chapter shows that advertising photography did not merely follow media transformations; it also played an active role in shaping new regimes of visibility and aesthetic experience. The rise of immersive practices and the reconfiguration of production through artificial intelligence and augmented reality point to a new cycle of experimentation, in which the photographer is repositioned as a curator of multisensory visual experiences.